WHAT IS THE IMPACT OF MONEY SUPPLY, INFLATION, AND EXCHANGE RATE ON ECONOMIC GROWTH IN NIGERIA UNDER APC GOVERNANCE (2015–2023)? - Abass Adekunle Adewale (Journal of Business And Entrepreneurship, 2025)
This paper discusses the correlation between the major macroeconomic factors of money supply, inflation rate, and exchange rate with the economic growth in Nigeria under the All Progressives Congress (APC) government from 2015 to 2023. This was a time when there was the constant inflationary pressure, exchange rate fluctuation, and the continuous increase in money supply, which put people into question on how they were able to stimulate real economic growth. The research design adopted is ex-post facto research design based on the annual secondary data collected on the Central Bank of Nigeria (CBN) Statistical Bulletin. The effect of money supply, inflation rate and the exchange rate on Real Gross Domestic Product (RGDP) was assessed using multiple regression analysis using Ordinary Least Squares (OLS). Statistical analysis was done through IBM SPSS with the help of descriptive statistics and diagnostic tests to determine the reliability of the model. The results indicate that money supply and inflation rate have negative but statistically non-significant relationships with economic growth. Exchange rate has a positive correlation with RGDP and is near to being statistically significant, indicating that currency depreciation might have given weak growth stimulus over the period. Altogether, the results suggest that monetary policy did not play a crucial role in stimulating economic growth during the APC rule. The paper suggests that policymakers need to go beyond monetary policies and implement structural and institutional reforms in order to attain sustainable economic growth.